Geographic region, student loans, and college graduation rates. (20th May 2020) - Mohundro, J.D.; Joanis, Steve; Burnley, James
Student loan debt has become an increasingly important topic among American students, families, politicians, and economists. These student loans are even more concerning for those who do not complete their course of education and are left with reduced earning potential. Although an expansive collection of scholarly research has examined the outcomes - both financial and psychological - of student debt burdens, very few studies have considered the combined effects of endogenous and exogenous characteristics on graduation likelihood. To this end, we conducted a series of analyses to test multiple environmental variables' influence on graduation rates and student loan levels. We found out that school size and type, student background, and regional factors all heavily influenced both graduation rates and student loan debt.